Venture capital and high technology entrepreneurship - Florida, Richard; Kenney, Martin (Journal of Business Venturing, 1988)
Venture capital clearly plays an important role in high technology entrepreneurship. The purpose of this article is to explain the differences among various venture capital complexes focusing on where venture capital is important to innovation and entrepreneurship and conversely where it is not. We do so through an empirical and historical examination of the seven most important venture capital complexes: California (San Francisco/ Silicon Valley), Massachusetts (Boston), New York, Illinois (Chicago), Texas, Connecticut, and Minnesota (Minneapolis). We establish a three-part tripartite typology for explaining the differences between these venture capital complexes: 1) technology-oriented complexes are located close to concentrations of high technology intensive businesses, invest most of their funds locally, and are net attractors of capital; 2) finance-oriented complexes are located around financial institutions and export their capital; and 3) hybrid complexes mix characteristics of both technology and finance-oriented venturing. Our findings have a series of important practical implications. Although venture capital is not absolutely necessary to facilitate high technology entepreneurship, well-developed venture capital networks provide tremendous incentives for entrepreneurship by lowering the difficulties of entering an industry. Venture capitalists use both their experience and their contacts to reduce many of the information and opportunity costs associated with new business formation. The importance of contact networks and information to both deal flow and investment monitoring goes a low way toward explaining why venture capitalists cluster tightly together. The availability of venture capital also attracts entrepreneurs and high quality personnel to a region creating a virtuous circle of new enterprise formation, innovation, and economic development. Private, nonprofit, and subsidized public efforts aimed at providing venture capital and stimulating high technology entrepreneurship must confront the fact that venture capital alone will not magically generate entrepreneurship and economic development. It is important that such efforts recognize the nonfinancial side of venture investing and attract experienced personnel who can tap into established entrepreneurial networks and secure coinvestors. More significantly, establishing public venture funding in an area lacking the requisite entrepreneurial climate or technology infrastructure may create a “catch 22” situation where locally oriented funds invest in bad deals or where venture capital is simply exported to established high technology regions.